2014
DOI: 10.1128/aem.02395-14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nicotine on Streptococcus gordonii Growth, Biofilm Formation, and Cell Aggregation

Abstract: e Streptococcus gordonii is a commensal species of human oral flora. It initiates dental biofilm formation and provides binding sites for later colonizers to attach to and generate mature biofilm. Smoking is the second highest risk factor for periodontal disease, and cigarette smoke extract has been reported to facilitate Porphyromonas gingivalis-S. gordonii dual-species biofilm formation. Our hypothesis is that nicotine, one of the most important and active components of tobacco, stimulates S. gordonii multip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
51
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 37 publications
5
51
0
2
Order By: Relevance
“…These findings suggest that this may have resulted from the lower pH or moisture content in the snus and chewing tobacco samples or from the presence of antimicrobial compounds in these products. For example, nicotine has been shown to impact the growth of certain bacteria associated with dental caries (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that this may have resulted from the lower pH or moisture content in the snus and chewing tobacco samples or from the presence of antimicrobial compounds in these products. For example, nicotine has been shown to impact the growth of certain bacteria associated with dental caries (36,37).…”
Section: Discussionmentioning
confidence: 99%
“…mutans was grown in TSB plus 1% sucrose (TSBS) with 0, 1, 2 and 4 mg/ml nicotine The image processing and analysis program was written according to Heydorn's principles (19) by MATLAB ÂŽ R2012a (The MathWorks, Inc.) via the codes reported before (20). …”
Section: Confocal Laser Scanning Microscopy (Clsm)mentioning
confidence: 99%
“…The q-PCR protocol described previously was followed (20 estimate a unit cell of LDH activity. The crystal violet assay was processed as described before (11).…”
Section: Quantitative-pcr (Q-pcr)mentioning
confidence: 99%
“…Huang et al 37) also reported that under the environment of nicotine extract presence, heterogeneous biofilm of P.…”
Section: Discussionmentioning
confidence: 99%
“…gordonii is an early colony and it provides a place where bacteria causing periodontal disease could be attached to biofilm 37) . F. nucleatum helps bacteria causing periodontal disease attach to teeth or oral epithelial cells at the middle point of physical interaction of gram positive bacteria and gram negative bacteria.…”
Section: Discussionmentioning
confidence: 99%